Echocardiographic assessment of Diastolic Function in patients with Atrial Fibrillation - Adhikaree, Ajay; Malla, Rabi; Sah, Ram Kishor; Maskey, Arun; Rajbhandari, Sujeeb; Sharma, Deewakar; Gautam, Binayak; Najmy, Shaneez (Nepalese Heart Journal, 2019)
Background and Aims: Echocardiographic assessment of left ventricular diastolic function in patients with atrial fibrillation is a challenge as loss of atrial kick (A wave), beat to beat variability and left atrium enlargement despite normal atrial pressure make usual guideline based estimation difficult and inaccurate. Hence adoption of additional echocardiography parameters are necessary which are tricky and have varied results. Hence the aim of this study was to study various aspects of diastolic function in patients with atrial fibrillation. Methods: It was a hospital based prospective cross-sectional observational study conducted at cardiology unit, National Academy of Medical Sciences, Kathmandu and Shahid Gangalal National Heart Center, Kathmandu from 1st July 2018 to 30th June 2019. Results: Total of 92 patients were studied. About one third (34.8%) had diastolic dysfunction. Ratio of E/e’(14.65 ± 2.21 Vs 7.66 ± 1.18) , E/Vp (1.57 ± 0.14 Vs 1.20 ± 0.11), isovolumetric relaxation time (53.06 ± 13.82ms Vs 89.33 ± 9.88ms) and deceleration time of pulmonary venous diastolic wave (203.09 ± 26.13ms Vs 292.25 ± 36.32ms) were significantly different in patients with diastolic dysfunction compared to patients without diastolic dysfunction with sensitivity of 90.6%, 84.4%, 81.2% and 78.1% respectively. Conclusion: Diastolic dysfunction is a common entity in patients with atrial fibrillation. Echocardiography parameters like E/e’ ratio, isovolumetric relaxation time, E/Vp ratio and deceleration time of diastolic pulmonary wave were highly sensitive in detection of diastolic dysfunction.